Phylogenomic, Biogeographic, and Evolutionary Research Trends in Arachnology - Kuntner, Matjaž (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book focuses on systematics, biogeography, and evolution of arachnids, a group of ancient chelicerate lineages that have taken on terrestrial lifestyles. The book opens with the questions of what arachnology represents, and where the field should go in the future. Twelve original contributions then dissect the current state-of-the-art in arachnological research. These papers provide innovative phylogenomic, evolutionary and biogeographic analyses and interpretations of new data and/or synthesize our knowledge to offer new directions for the future of arachnology.